LIP4 Is Involved in Triacylglycerol Degradation in Chlamydomonas reinhardtii. (22nd February 2019) - Warakanont, Jaruswan; Li-Beisson, Yonghua; Benning, Christoph
Abstract: Degradation of the storage compound triacylglycerol (TAG) is a crucial process in response to environmental stimuli. In microalgae, this process is important for re-growth when conditions become favorable after cells have experienced stresses. Mobilization of TAG is initiated by actions of lipases causing the release of glycerol and free fatty acids, which can be further broken down for energy production or recycled to synthesize membrane lipids. Although key enzymes in the process, TAG lipases remain to be characterized in the model green alga Chlamydomonas reinhardtii . Here, we describe the functional analysis of a putative TAG lipase, i.e. LIP4, which shares 44% amino acid identity with the major TAG lipase in Arabidopsis (SUGAR DEPENDENT1—SDP1). The LIP4 transcript level was downregulated during nitrogen deprivation when TAG accumulates, but was upregulated during nitrogen resupply (NR) when TAG was degraded. Both artificial microRNA and insertional mutants showed a delay in TAG mobilization during NR. The difference in TAG degradation was more pronounced when the cultures were incubated without acetate in the dark. Furthermore, the lip4 insertional mutants over-accumulated TAG during optimal growth conditions. Taken together, the results suggest to us that LIP4 likely acts as a TAG lipase and plays a role in TAG homeostasis in Chlamydomonas .